2015
DOI: 10.2337/db14-0704
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Role for Subcutaneous Adipose Tissue in Exercise-Induced Improvements in Glucose Homeostasis

Abstract: Exercise training improves whole-body glucose homeostasis through effects largely attributed to adaptations in skeletal muscle; however, training also affects other tissues, including adipose tissue. To determine whether exercise-induced adaptations to adipose tissue contribute to training-induced improvements in glucose homeostasis, subcutaneous white adipose tissue (scWAT) from exercise-trained or sedentary donor mice was transplanted into the visceral cavity of sedentary recipients. Remarkably, 9 days post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

19
360
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 260 publications
(386 citation statements)
references
References 49 publications
19
360
0
7
Order By: Relevance
“…26 Our work demonstrated that exercise training by voluntary running in a cage containing a wheel for only 11 d resulted in a marked upregulation of numerous beige adipocyte marker genes including Ucp1, Prdm16, Cidea, Elovl3, Pgc1a, Pparg, Cox8b, Dio2, otopetrin, and Tbx1. 21 The wheel cage-trained mice had dramatically increased UCP1 immunofluorescence and the presence of multilocular cells in the scWAT, all of which are consistent with the beiging of scWAT. 21 Thus, exercise training in rodents increases the presence of beige adipocytes in the subcutaneous adipose tissue depots.…”
Section: Effects Of Exercise On Watmentioning
confidence: 61%
See 4 more Smart Citations
“…26 Our work demonstrated that exercise training by voluntary running in a cage containing a wheel for only 11 d resulted in a marked upregulation of numerous beige adipocyte marker genes including Ucp1, Prdm16, Cidea, Elovl3, Pgc1a, Pparg, Cox8b, Dio2, otopetrin, and Tbx1. 21 The wheel cage-trained mice had dramatically increased UCP1 immunofluorescence and the presence of multilocular cells in the scWAT, all of which are consistent with the beiging of scWAT. 21 Thus, exercise training in rodents increases the presence of beige adipocytes in the subcutaneous adipose tissue depots.…”
Section: Effects Of Exercise On Watmentioning
confidence: 61%
“…21 The wheel cage-trained mice had dramatically increased UCP1 immunofluorescence and the presence of multilocular cells in the scWAT, all of which are consistent with the beiging of scWAT. 21 Thus, exercise training in rodents increases the presence of beige adipocytes in the subcutaneous adipose tissue depots.…”
Section: Effects Of Exercise On Watmentioning
confidence: 61%
See 3 more Smart Citations